2015
DOI: 10.1111/ijd.12887
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and serological efficacy of topical calcineurin inhibitors in oral lichen planus: a prospective randomized controlled trial

Abstract: Oral lichen planus (OLP) is a T-cell-mediated disease characterized by immune-mediated basal cell degeneration releasing interleukins (ILs) such as IL-6 and IL-8 into the circulation. Their serum levels reportedly reflect disease activity. Although many therapeutic options are available, none are curative. We compared the efficacy of tacrolimus 0.1% ointment and pimecrolimus 1% cream in OLP and correlated with serum IL-6 and IL-8 levels before and after treatment. Forty patients with symptomatic OLP were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 19 publications
0
37
1
1
Order By: Relevance
“…All 25 examined studies were randomized controlled trials; 22 of these were parallel group studies, 1 was a crosssectional study [21] and 2 were split-mouth design studies [11,12]. Furthermore, 4 were single-blind studies [14,19,24,25] and 9 were double-blind studies [10,16,[20][21][22][23][26][27][28]. Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 25 examined studies were randomized controlled trials; 22 of these were parallel group studies, 1 was a crosssectional study [21] and 2 were split-mouth design studies [11,12]. Furthermore, 4 were single-blind studies [14,19,24,25] and 9 were double-blind studies [10,16,[20][21][22][23][26][27][28]. Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes evaluated regarding these therapeutic approaches were different; in relation to the symptomatologygenerally characterized by a burning sensation and pain -the majority of studies evaluated symptoms by using the Visual Analog Scale (VAS), and 4 studies used the Numerical Rating Scale (NRS) [10,11,18,19]. Only two studies did not consider symptomatology as an outcome [15,27], while the results of one study were based exclusively on evaluating the improvement of symptoms, using the VAS [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized controlled study (23) suggested that pimecrolimus 1% cream is equally effective as tacrolimus 0.1% ointment in OLP. No severe adverse effects necessitating stopping treatment were observed in the two groups.…”
Section: Discussionmentioning
confidence: 99%